The Healthiest Diet for You Scientific Aspects - Simopoulos, Artemis P. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Healthiest Diet for You: Scientific Aspects is unique in a sense because it focuses on the most recent advances in Nutrition, Metabolism, and Genetics that are the basic components of Personalized Nutrition. The book also emphasizes the importance of evolutionary aspects of diet and exercise and the need to select foods that are consistent with the evolutionary aspects of diet because these are the foods that contain the nutrients that our genes are programmed to respond. This book is the antidote to ultra-processed foods and imitation foods that are proinflammatory and contribute to increases in chronic diseases, especially cardiovascular disease. It is a book for Health! The aim of the book is to provide readers with the basic factual information necessary to comprehend the enormity and potential effects of nutrients and foods on overall health and well-being. This book should be of interest to the educated public, teachers, health professionals, physicians, medical students, nutritionists, dietitians, historians and policy makers.